The reactivity of pyridine in cold interstellar environments: The reaction of pyridine with the CN radical - Heitkämper, Juliane; Suchaneck, Sarah; García de la Concepción, Juan; Kästner, Johannes; Molpeceres, Germán (Frontiers in Astronomy and Space Sciences, 2022)
The recent detection of cyclic species in cold interstellar environments is an exciting discovery with yet many unknowns to be solved. Among them, the presence of aromatic heterocycles in space would act as an indirect evidence of the presence of precursors of nucleotides. The seeming absence of these species in the observations poses a fascinating conundrum that can be tackled with computational insights. Whilst many arguments can be given to explain the absence of heterocycles in space, one of the possible scenarios involves fast chemical conversion and formation of new species to be detected. We have tested this hypothesis for the reaction of pyridine with the CN radical to find possible scenarios in which the detectability of pyridine, as an archetypical heterocycle, could be enhanced or diminished via chemical conversions. Using a combination of ab-initio characterization of the reactive potential energy surface and kinetic and chemical simulations, we have established that pyridine does react very fast with CN radicals, estimating that the studied reactions is \rv{between 2.5--4.5} times faster in pyridine than in benzene, with a total loss rate constant of 1.33$×$ 10$^{-9}$ cm$^{3}$s$^{-1}$ \rv{at 30 K, with an almost null temperature dependence in the [30--150] K range}. Addition reactions forming 1,2,3-cyanopyridine are favored over abstraction reactions or the formation of isocyanides. Besides, for 1 and 2-cyanopyridine there is an increase in the total dipole moment with respect to pyridine, which can help in their detection. However, the reaction is not site specific, and equal amounts of 1,2,3-cyanopyridine are formed during the reaction, diluting the abundance of all the individual pyridine derivatives.